Terrestrial arthropods from tree canopies in the Pantanal of Mato Grosso, Brazil - Marques,Marinêz Isaac (2006)
Terrestrial arthropods from tree canopies in the Pantanal of Mato Grosso, Brazil. This study represents a contribution to the knowledge of the diversity of arthropods associated to the canopy of Vochysia divergens Pohl (Vochysiaceae). Three trees individuals were sampled during two seasonal periods in this region: a) by spraying one tree canopy during high water (February); b) by fogging two tree canopies during low water (September/October). The 15,744 arthropods (183.2±38.9 individuals/m²) obtained from all three trees (86 m²) represented 20 taxonomic orders, 87.1% were Insecta, and 12.9% Arachnida. The dominant groups were Hymenoptera (48.5%; 88.9 individuals/m²), mostly Formicidae (44.5%; 81.4 individuals/m²), followed by Coleoptera (14.0%; 25.5 individuals/m²) and Araneae (10.2%; 19.5 individuals/m²), together representing 62.5% of the total catch. Fourteen (70%) of all orders occurred on three trees. Dermaptera, Isoptera, Neuroptera, Odonata, Plecoptera and Trichoptera were collected from only one tree. Of the total, 2,197 adult Coleoptera collected (25.5±11.3 individuals/m²), 99% were assigned to 32 families and 256 morphospecies. Nitidulidae (17.9% of the total catch; 4.6 individuals/m²), Anobiidae (16.7%; 4.3 individuals/m²), Curculionidae (13.2%; 3.4 individuals/m²) and Meloidae (11.4%; 2.9 individuals/m²) dominated. The communitiy of adult Coleoptera on V. divergens indicated a dominance of herbivores (37.8% of the total catch, 127 spp.) and predators (35.2%, 82 spp.), followed by saprophages (16.2%, 32 spp.) and fungivores (10.8%, 15 spp.). The influence of the flood pulse on the community of arboreal arthropods in V. divergens is indicated by the seasonal variation in evaluated groups, causing changes in their structure and composition.